What is the Main Processing Factor Influencing Staphylococcus Species Diversity in Different Manufacturing Units?. Issue 10 (16th September 2019) - Fraqueza, Maria João; Rocha, João Miguel; Laranjo, Marta; Potes, Maria Eduarda; Fialho, Ana Rita; Fernandes, Maria José; Fernandes, Maria Helena; Barreto, António; Semedo‐Lemsaddek, Teresa; Elias, Miguel
Abstract : Abstract: The microbiota of traditional dry‐cured sausages and industrial environment was assessed to characterize the diversity of coagulase‐negative staphylococci (CNS), and establish potential relationships with hygiene level or technological characteristics. Eight processing units from South Portugal were audited according to a checklist of requirements. Environmental and products' samples at different production stages were evaluated regarding hygiene and safety criteria. CNS were recovered, characterized, and their potential use as starters evaluated. Low genetic diversity was observed for Staphylococcus xylosus, whereas Staphylococcus equorum showed diverse genetic profiles. Staphylococcus xylosus predominated in products with a long period of cold smoking, Staphylococcus saprophyticus in products with a long period of hot smoking, Staphylococcus epidermidis in products with a short period of cold smoking, and S. equorum in nonsmoked products. Most S. xylosus were resistant to tetracycline, whereas S. equorum were susceptible. Antibioresistance restricted the selection of starters due to safety recommendations. Practical Application: The present manuscript highlighted a few staphylococci strains that could potentially be used as starter cultures in fermented meat products. These selected strains do not show resistance to antimicrobials, exhibit adequate technological features, and are well adapted to the industrial environments of meat processing industries using different processing technologies. Therefore, the selected strains ready to be used in the manufacturing of traditional fermented meat products to ensure safety, standardize product properties, and shorten ripening.